Rethinking the Larger Pattern of the American Interest in the Arab Gulf - Hasnan Bachtiar (Jurnal Ilmiah Hubungan Internasional, 2020)
This paper evaluates the larger pattern of American interest in the Arab Gulf. It questions whether the pattern is based on ideological or economic interest. It also critically examines various data and interprets following their (data) social, economic and political interlinks and special topics that have been significantly proposed in the state policy. This paper argues that the US foreign policy represents two larger directions of its interest: economy and ideology. Both have linked together and interrelatedly have determined and have been determined by strategic culture of the states in the region and its complexities covering all national, interstate, regional, broader regional (Middle East) and global levels. This paper also arguably states that there is no single interest that can be oversimplified, but it has remained highly dynamic or has demonstrated multiple complexities of the interest in which they are represented by issues of oil, war on terrorism, nuclear weapon and Israel.